The Academic Game - Roberts-Wilbur, Janice; Wilbur, Michael (My University, 1986)
The authors created a Checklist of Self-Defeating Behaviors and Assumptions for athletes with 33 items based on their experiences teaching a freshman transition class and observing athletes throughout the semester. They highlighted athletes' challenges transitioning from high school to college and noted a general lack of knowledge about the college experience for freshman athletes.
Keywords: academic support; skills; transitions; freshmen